Modelling the health labour market outlook in Kenya: Supply, needs and investment requirements for health workers, 2021-2035. - James Avoka Asamani; Brendan Kwesiga; Sunny C Okoroafor; Evalyne Chagina; Joel Gondi; Zeinab Gura; Francis Motiri; Nakato Jumba; Teresa Ogumbo; Nkatha Mutungi; Stephen Muleshe; Yusuf Suraw; et al. (PLOS Global Public Health)
Kenya is committed to achieving Universal Health Coverage (UHC) within its devolved health system in which significant investments have been made in health infrastructure, workforce development, and service delivery. Despite these efforts, the country faces considerable health workforce challenges. To address these, the Ministry of Health undertook a comprehensive Health Labour Market Analysis (HLMA) in 2022 to generate evidence supporting the development of responsive health workforce policies. This paper presents findings of a modelling exercise to understand the health labour market outlook. As part of a comprehensive HLMA, a validated needs-based health workforce modelling framework was applied to project the supply, needs, and investment requirements. Data was triangulated from multiple sources through desk reviews and group modelling by an expert technical working group constituted to undertake the study. The analysis considered disease burden, population growth, service delivery models, and health worker productivity, to assess the future health workforce needed. Kenya's health workforce is growing, with approximately 7,650 new workers added annually, resulting in an estimated 3.4% annual growth. By 2025, the health workforce is projected to reach 226,434, increasing to 263,700 by 2030. However, Kenya required a minimum of 254,220 health workers in 2021 to make substantial progress toward UHC. The cumulative need could rise to 476,278 by 2035. In 2021, Kenya had a needs-based shortage of nearly 60,000 health professionals, which could increase to 114,352 by 2030. The financial space for health workforce was estimated at US$2.29 billion in 2021 and is projected to rise to US$3.58 billion by 2030, but the required wage bill potentially reaching US$3.9 billion. Kenya must significantly increase investments in its health workforce to meet UHC goals. Both public and private sectors need to contribute more, with the public sector requiring a health workforce budget increase of 10.5% annually to bridge the projected funding gap.